Best Management Practices in Sri Lanka:: Manufacturing Sector - Fonseka, Tilak (Journal of Comparative International Management)

(untitled) (Management Futures, 1999)
This paper describes and analyzes the best management practices of a few selected firms in Sri Lanka's manufacturing sector, and compares these practices with those found in subsidiaries of major multinational corporations operating in Sri Lanka.